DAMPAK KEBERADAAN KAWASAN INDUSTRI TERHADAP GUNA LAHAN DI KELURAHAN WAY LUNIK KECAMATAN PANJANG KOTA BANDAR LAMPUNG - Dewi Mazab Suni; Lutfi Setianingrum; Tetty Harahap (Jurnal Perencanaan dan Pengembangan Kebijakan, 2023)
Based on the Regional Spatial Plan (RTRW) for the City of Bandar Lampung in 2011-2030, there is a medium-sized industrial area and warehouse area, one of which is in Way Lunik Village. Based on the facts in the field industry agglomerates and uses land for industry. The purpose of this study is to describe the impact of industrial existence on land use in Way Lunik Village, Panjang District, Bandar Lampung City. Researchers used Spatial Analysis with map overlay analysis techniques to see land use conditions in 2001-2021. Furthermore, using descriptive qualitative analysis with sampling techniques, namely purposive sampling and snowball sampling to identify the impact of the existence of industrial estates. Based on the analysis that has been carried out, land use changes change the physical and non-physical land use conditions. There are changes in land use and changes in economic activity. The dominant land use change is the change in land use to industry. Changes in economic activity are directly reflected in changes in land use, changes in the function of residential buildings, changes in yard area, distance between buildings, land ownership, land prices, accessibility, facilities and infrastructure, and the most important community activities.